2017
DOI: 10.2174/0929867324666170724142641
|View full text |Cite
|
Sign up to set email alerts
|

Pro-angiogenic Molecules for Therapeutic Angiogenesis

Abstract: This review focuses on importance of various proangiogenic factors, with reference to therapeutic angiogenesis. Thorough analysis of clinical data reveals the dearth of a defined system for proangiogenic growth factor delivery. Designing of a biomaterial based paradigm for growth factor therapy, might help in enhancing clinical translation of therapeutic angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In addition to growth factors and cytokines, electrospun nanofibers have been utilized to load and control the release of angiogenic small molecules (e.g., angiogenin) and phytochemicals (e.g., curcumin) in order to accelerate the healing process [38,39]. However, it should be highlighted that the angiogenic efficacy of such substances is strongly dose-dependent [40,41]. It is worth mentioning that surface functionalization of nanofibrous scaffolds by angiogenic bioactive molecules was also proven as a feasible approach for promoting tissue repair and regeneration [42,43].…”
Section: Fiber Orientationmentioning
confidence: 99%
“…In addition to growth factors and cytokines, electrospun nanofibers have been utilized to load and control the release of angiogenic small molecules (e.g., angiogenin) and phytochemicals (e.g., curcumin) in order to accelerate the healing process [38,39]. However, it should be highlighted that the angiogenic efficacy of such substances is strongly dose-dependent [40,41]. It is worth mentioning that surface functionalization of nanofibrous scaffolds by angiogenic bioactive molecules was also proven as a feasible approach for promoting tissue repair and regeneration [42,43].…”
Section: Fiber Orientationmentioning
confidence: 99%
“…Use of angiosuppressive compounds to inhibit neovascularization can potentially prevent or reduce such proliferations, thus the risk of cancer . Meanwhile, pro‐angiogenesis treatment is gaining attention, not just for wound healing but also for tissue and organ regeneration, especially for damaged or abnormal cardiovascular system and age‐related ischemia …”
Section: Resultsmentioning
confidence: 99%
“…[53][54][55] Meanwhile, pro-angiogenesis treatment is gaining attention, not just for wound healing but also for tissue and organ regeneration, especially for damaged or abnormal cardiovascular system and age-related ischemia. [56][57][58][59]…”
Section: Anti-angiogenic Activitymentioning
confidence: 99%
“…Histological analysis of ischemic skin showed that tissues from the CD34+ Group contained more CD31+ cells than those from the ADSC Group. ADSC have been reported to have angiogenic effects by secreting VEGF, bFGF and other growth factors [29,30] . In our ex vivo study, we found that adipose-derived CD34+ cells expressed higher levels of VEGF and bFGF mRNA than ADSCs, as well as the related secreted proteins.…”
Section: Discussionmentioning
confidence: 99%